2009
DOI: 10.1002/dc.21273
|View full text |Cite
|
Sign up to set email alerts
|

Atypical glandular cells (AGC): ThinPrep Imaging System (TIS), manual screening (MS), and correlation with Hybrid Capture 2 (HC2) HPV DNA testing

Abstract: TIS and MS are comparable in the detection of AGC representing squamous histology and the addition of HPV DNA testing does not differentially improve performance. Although the MS group harbored more glandular pathology, the differences in the detection of AIS were not statistically significant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
2
3
0
Order By: Relevance
“…Fortunately, a number of studies, using various designs, found that the Imager algorithm does in fact identify and show to the screener abnormal glandular cells in most cases, resulting in no significant decrease in the detection of invasive or in situ adenocarcinoma when using this method. 3,[8][9][10] In one study, the sensitivity rate was found to be approximately similar to our study. TIS was able to identify atypical cells in 97% of these cases (68 of 70 cases) with a total number of 124 cases however they find 9 additional positive cases.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Fortunately, a number of studies, using various designs, found that the Imager algorithm does in fact identify and show to the screener abnormal glandular cells in most cases, resulting in no significant decrease in the detection of invasive or in situ adenocarcinoma when using this method. 3,[8][9][10] In one study, the sensitivity rate was found to be approximately similar to our study. TIS was able to identify atypical cells in 97% of these cases (68 of 70 cases) with a total number of 124 cases however they find 9 additional positive cases.…”
Section: Discussionsupporting
confidence: 88%
“…The widespread adoption of Imager led to some concern that the algorithm might not be optimal for the detection of glandular abnormalities. Fortunately, a number of studies, using various designs, found that the Imager algorithm does in fact identify and show to the screener abnormal glandular cells in most cases, resulting in no significant decrease in the detection of invasive or in situ adenocarcinoma when using this method 3,8–10 . In one study, the sensitivity rate was found to be approximately similar to our study.…”
Section: Discussionsupporting
confidence: 78%
“…Fortunately, a number of studies, using various designs, found that the Imager algorithm does in fact identify and show to the cytotechnologist abnormal glandular cells in most cases, resulting in no significant decrease in detection of invasive or in situ adenocarcinoma when using this method. [34][35][36] Likewise, detection of pathogenic organisms, though much less important, also appears not to decrease significantly when using the Imager for screening. 19,32 The Imager was the first commercial system to achieve significant commercial success.…”
Section: Thinprep Imaging System (Imager)mentioning
confidence: 99%
“…Since cases with no abnormalities in the 22 FOV selected by the Imager can be signed out as negative, many investigators feared that atypical glandular cells might be ignored by the algorithm and therefore would not be shown to cytotechnologists, resulting in false‐negative results. Fortunately, a number of studies, using various designs, found that the Imager algorithm does in fact identify and show to the cytotechnologist abnormal glandular cells in most cases, resulting in no significant decrease in detection of invasive or in situ adenocarcinoma when using this method . Likewise, detection of pathogenic organisms, though much less important, also appears not to decrease significantly when using the Imager for screening …”
Section: Papnetmentioning
confidence: 99%
“…The ThinPrep Papanicolaou-stained (Pap) smear has been one of the precancerous diagnosis methods of high-risk cervical carcinoma and has been widely used to screen the cervical cancer currently since it was developed in the 1990s [1] , [2] , [3] . ThinPrep liquid-based cytology has become a preferred method, of which samples were fixed in time, and blood, mucus and unstructured pieces were eliminated from the specimen.…”
Section: Introductionmentioning
confidence: 99%